Satellite tag derived data from two Antarctic blue whales (Balaenoptera musculus intermedia) tagged in the east Antarctic sector of the Southern Ocean - Virginia Andrews-Goff; Elanor Bell; Brian Miller; Simon Wotherspoon; Michael Double (Biodiversity Data Journal, 2022)
Satellite tags were deployed on two Antarctic blue whales (Balaenoptera musculus intermedia) in the east Antarctic sector of the Southern Ocean as part of the International Whaling Commission’s Southern Ocean Research Partnership initiative. The satellite tracks generated are the first and currently, the only, satellite telemetry data that exist for this critically endangered species. These data provide valuable insights into the movements of Antarctic blue whales on their Antarctic feeding ground. The data were collected between February and April 2013 and span a 110° longitudinal range.This dataset is the first and only detailed movement data that exist for this critically endangered species. As such, this dataset provides the first measures of movement rates (distances travelled, speeds) and movement behaviour (distinguishing transit behaviour from area restricted search behaviour) within the Southern Ocean. These movement-based measures are critical to the ongoing management of Antarctic blue whales as they recover from commercial whaling as they provide insight into foraging behaviour, habitat use, population structure and overlap with anthropogenic threats.